A New Concept of Color Fidelity for Museum Lighting: Based on an Experiment in the Sistine Chapel. Issue 1 (2nd April 2016) - Schanda, J.; Csuti, P.; Szabó, F.
Abstract: In almost all color rendering calculations, where a reference illuminant is needed, a Planckian or daylight spectrum of the same correlated color temperature as that of the test source is used (a few methods tried to use only D65 or a very restricted number of test illuminants, but these have not received general acceptance). In this article, a new calculation method of color fidelity is introduced that uses modern colorimetric practice in order to reproduce the colors of the painting as seen under the light under which it was painted (probably daylight for a picture prepared before the end of the 19th Century) but keeping the correlated color temperature of the light source warm-white for museum lighting. The principles of corresponding color color rendering are described and an Excel workbook is provided for further testing purposes.